2009
DOI: 10.1007/s10552-009-9406-z
|View full text |Cite
|
Sign up to set email alerts
|

Legume intake and the risk of cancer: a multisite case–control study in Uruguay

Abstract: Background Previous studies have suggested that a high intake of legumes may decrease the risk of stomach and prostate cancer and some other cancers. However, the evidence is still limited. To further explore the association between legume intake and cancer risk we conducted a case-control study of 11 cancer sites in Uruguay between 1996 and 2004, including 3,539 cancer cases and 2,032 hospital controls. Results The highest versus the lowest tertile of legume intake was associated with a significant decrease i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
98
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(108 citation statements)
references
References 80 publications
(100 reference statements)
5
98
2
1
Order By: Relevance
“…Previous studies have suggested that eggs consumption may increase the risk of colorectal cancer and some other cancers (Steinmetz et al, 1994;Aune et al, 2009). In the present meta-analysis, we found no statistically significant positive association between high intake of eggs and risk of prostate cancer.…”
Section: Discussioncontrasting
confidence: 82%
“…Previous studies have suggested that eggs consumption may increase the risk of colorectal cancer and some other cancers (Steinmetz et al, 1994;Aune et al, 2009). In the present meta-analysis, we found no statistically significant positive association between high intake of eggs and risk of prostate cancer.…”
Section: Discussioncontrasting
confidence: 82%
“…The associations of dietary factors with breast cancer did not vary by menopausal status. Other studies, mostly conducted in Asian populations, have found the same protective effect (Malin et al, 2003;Gaudet et al, 2004;Shannon et al, 2005;Do et al, 2007;Aune et al, 2009;Zhang et al, 2009). A meta-analysis of 23 studies also concluded that vegetable intake reduced breast cancer risk by 20% to 25% (Gaudet et al, 2004).…”
Section: Discussionmentioning
confidence: 89%
“…Breast cancer, the most frequent malignancies among women is the leading cause of cancer related death, resulting from the metastatic development of primary stage of cell tumors (Jemal et al, 2006). Application of plants in treatment of different diseases including cancers is inevitable and it seems to be the basis for modern medical science, as they are considered to be great sources of new drugs (Jones et al, 2006;Kim, 2008;Aune et al, 2009;Hasan et al, 2011;Woo and Kim, 2011).…”
Section: Introductionmentioning
confidence: 99%